Ternary positive electrode material co-modified by niobium and boron, preparation method thereof, positive electrode sheet and secondary battery

CN122950468APending Publication Date: 2026-10-20HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611140981.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]本发明的主要目的在于提供一种铌硼共改性三元正极材料及其制备方法、正极电极片以及二次电池,以解决现有技术中的三元正极材料的单晶颗粒生长动力学不足、晶体结构差、锂离子传输动力学滞后的问题

Benefits of technology

[0019]应用本发明的技术方案,采用铌(Nb)与硼(B)作为共掺杂元素,并通过控制掺杂量在极低摩尔比例范围内、优化锂金属比及三元金属组分比例,以及确保晶格结构中Nb与B原子的原子级均匀分布,达到了在不破坏层状结构的前提下协同稳定晶格、抑制阳离子混排与促进锂离子迁移的目的,从而实现了在高电压循环下容量保持率显著提升、倍率性能增强与弱化结构衰减的技术效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a niobium-boron co-modified ternary cathode material, its preparation method, cathode electrode sheet, and secondary battery. The chemical formula of the niobium-boron co-modified ternary cathode material is Li. a (Ni x Co y Mn z ) 1‑b‑c Nb b B c O2, where 1.0≤a≤1.10, 0.6≤x<1, 0.01≤y≤0.2, 0.01≤z≤0.3, x+y+z=1, 0<b≤0.00006, 0<c≤0.0003. This invention uses niobium and boron as co-doping elements. By controlling the doping amount within an extremely low molar ratio range, optimizing the lithium metal ratio and the ternary metal component ratio, and ensuring the atomic-level uniform distribution of Nb and B atoms in the crystal lattice structure, it achieves the goal of synergistically stabilizing the crystal lattice, suppressing cation mixing, and promoting lithium-ion migration without destroying the layered structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary batteries, and more specifically, to a niobium-boron co-modified ternary cathode material, its preparation method, cathode electrode sheet, and secondary battery. Background Technology

[0002] Nickel-cobalt-manganese (NCM) ternary cathode materials play a decisive role in the energy density, safety, and lifespan of lithium-ion batteries. However, with the increasing demand for next-generation lithium-ion batteries, high-nickel cathode materials are achieving higher energy densities by increasing nickel content and raising the upper limit of the operating voltage range, which poses a significant challenge to the structural stability of the materials.

[0003] Compared with traditional polycrystalline ternary (PNCMs) materials, single-crystal ternary (SNCMs) cathode materials have a single crystal structure without grain boundaries, which can effectively alleviate the stress concentration problem during cycling, suppress particle breakage and structural collapse, and significantly improve the structure and cycling stability of the material. Therefore, it has become an important development trend to break through the performance bottleneck of ternary cathode materials. However, the pure phase or single-element doped ternary single-crystal cathode materials prepared by existing technologies still face several core technical bottlenecks: (1) Insufficient growth kinetics of single crystal particles. Pure phase ternary materials are prone to slow particle growth during high-temperature sintering or crystal nucleation. Problems such as slow speed, uneven size, and irregular morphology lead to poor material dispersion, making it difficult to achieve large-scale preparation; (2) Poor lattice structure stability: during high-voltage charging and discharging and long-term lithium insertion and extraction, the ternary layered structure is prone to lattice distortion and transformation of the layered structure into spinel or rock salt phase, resulting in irreversible capacity decay; (3) Lagging lithium-ion transport kinetics: the lithium-ion migration path in the pure phase lattice is easily hindered by factors such as lattice defects and disordered atomic arrangement, leading to an increase in ion migration energy barrier, poor material rate performance, and difficulty in meeting the needs of fast charging of new energy vehicles and high power output of energy storage systems. Therefore, the structure of existing SNCMs still needs to be further optimized to improve its practical value.

[0004] While current strategies such as sintering, doping, and coating are employed to modify single-crystal materials, the trade-off between structural stability and electrochemical performance remains unresolved. In contrast, coating is highly effective in addressing surface issues, but its influence on crystal structure is extremely limited. Since bulk structure is also a core factor determining material performance, further optimization through doping is necessary. While single-element doping (such as doping with niobium, boron, aluminum, or magnesium) can improve material performance in specific aspects, it has significant limitations. It cannot achieve the synergistic optimization of the three major objectives of "promoting single-crystal growth, enhancing lattice structure, and accelerating lithium-ion transport," thus limiting the overall performance improvement and making it difficult to meet the stringent requirements of high-end energy storage scenarios for cathode materials.

[0005] In summary, developing a composite modification strategy with synergistic effects, by rationally selecting doping elements and controlling their ratios, and utilizing the synergistic effect between different elements to simultaneously solve the three core problems of single crystal growth kinetics, lattice stability, and lithium-ion transport efficiency, thereby comprehensively improving the overall electrochemical performance of ternary single-crystal cathode materials, has become a technical challenge that urgently needs to be overcome in the field of ternary cathode materials. This is of great significance for promoting the development of lithium-ion batteries towards higher energy density, longer cycle life, and higher power output. Summary of the Invention

[0006] The main objective of this invention is to provide a niobium-boron co-modified ternary cathode material and its preparation method, cathode electrode sheet, and secondary battery, in order to solve the problems of insufficient single-crystal particle growth kinetics, poor crystal structure, and lag in lithium-ion transport kinetics in existing ternary cathode materials.

[0007] To achieve the above objectives, a first aspect of the present invention provides a niobium-boron co-modified ternary cathode material, the chemical formula of which is Li. a (Ni x Co y Mn z ) 1-b-c Nb b B c O2, where 1.0≤a≤1.10, 0.6≤x<1, 0.01≤y≤0.2, 0.01≤z≤0.3, x+y+z=1, 0<b≤0.00006, 0<c≤0.0003.

[0008] Furthermore, in the chemical formula of the niobium-boron co-modified ternary cathode material, 0.00002 < b ≤ 0.00006, and 0.0002 < c ≤ 0.0003.

[0009] Furthermore, the niobium-boron co-modified ternary cathode material is selected from Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99967 Nb 0.00003 B 0.0003 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99964 Nb 0.00006 B 0.0003 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99976 Nb 0.00004 B0.0002 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99968 Nb 0.00002 B 0.0003 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99977 Nb 0.00003 B 0.0002 One or more of O2.

[0010] A second aspect of the present invention provides a method for preparing the above-mentioned niobium-boron co-modified ternary cathode material, comprising: step S1, wherein a precursor, a lithium source, a first niobium source, and a first boron source are subjected to a first sintering treatment to obtain a first material; step S2, wherein the first material, a second niobium source, and a second boron source are subjected to a dispersion treatment, a freeze-microwave treatment, and a second sintering treatment in sequence to obtain a second material; and step S3, wherein the second material and a third boron source are subjected to a third sintering treatment to obtain the niobium-boron co-modified ternary cathode material.

[0011] Further, in step S1, based on the weight of the precursor as 100%, the amount of niobium added to the first niobium source is 0.05%~0.3%; and / or, the weight ratio of niobium in the first niobium source to boron in the first boron source is (0.8~1.2):(0.8~1.2); and / or, the sintering temperature of the first sintering treatment is 650℃~950℃, the sintering time is 5h~25h, and the first sintering treatment is carried out in an oxygen atmosphere; and / or, the heating rate of the first sintering treatment is 2℃ / min~7℃ / min.

[0012] Further, in step S1, the first sintering treatment includes two stages performed sequentially in an oxygen atmosphere: a first stage and a second stage. The sintering temperature in the first stage is 650℃~750℃, and the sintering time is 5h~10h. The sintering temperature in the second stage is 800℃~950℃, and the sintering time is 10h~15h. Preferably, the cell volume of the primary particles of the first material is 33.80 Å. 3 ~34.10Å 3 The roundness of the primary particles is 0.7~0.98, the aspect ratio is 1.0~1.3, and the particle size is 1.4μm~2.4μm.

[0013] Further, in step S2, the weight ratio of niobium in the first material, niobium in the second niobium source, and boron in the second boron source is 1:(0.001~0.005):(0.0005~0.001); and / or, the sintering temperature of the second sintering treatment is 500℃~700℃, the sintering time is 2h~8h, and the second sintering treatment is carried out in an oxygen atmosphere.

[0014] Furthermore, in step S2, the dispersion treatment is performed by ultrasonic-assisted wet ball milling, and the ball-to-material ratio used in the ultrasonic-assisted wet ball milling is (1~5):1, the solid-liquid ratio is 1:(3~10), the ball milling speed is 200r / min~500r / min, the ultrasonic power is 100W~500W, and the mixing time is 2h~5h; and / or, the freeze-microwave treatment includes: sequentially subjecting the mixed slurry obtained from the dispersion treatment to a freeze stage, a first microwave stage, and a second microwave stage; preferably, the temperature of the freeze stage is -40℃~-20℃, the vacuum degree is 10Pa~100Pa, and the time is 2h~4h; and / or, the microwave power used in the first microwave stage is 50W~150W, the temperature is 30℃~50℃, and the time is 0.5±0.1h; and / or, the microwave power used in the second microwave stage is 150W~300W, the temperature is 60℃~80℃, and the time is 0.5±0.1h.

[0015] Further, in step S3, based on the weight of the second material as 100%, the amount of boron added to the third boron source is 0.01%~0.03%; and / or, the sintering temperature of the third sintering treatment is 200℃~500℃, the sintering time is 2h~8h, and the third sintering treatment is carried out in an oxygen atmosphere.

[0016] Furthermore, the first niobium source and the second niobium source are each independently added in the form of at least one of nitrate, acetate, chloride, and oxide; and / or, the first boron source, the second boron source, and the third boron source are each independently boric acid and / or boron oxide; and / or, the precursor has the chemical formula Ni x Co y Mn z (OH)2, wherein 0.6≤x<1, 0.01≤y≤0.2, 0.01≤z≤0.3, and x+y+z=1; and / or, the lithium source is selected from one or more of lithium chloride, lithium acetate, lithium hydroxide and lithium carbonate; and / or, the ratio of the molar amount of lithium element in the lithium source to the molar amount of all metal elements in the precursor is (1~1.10):1.

[0017] A third aspect of the present invention provides a positive electrode sheet comprising the above-mentioned niobium-boron co-modified ternary positive electrode material; or, the positive electrode sheet comprising a niobium-boron co-modified ternary positive electrode material prepared by the above-mentioned method for preparing the niobium-boron co-modified ternary positive electrode material.

[0018] A fourth aspect of the present invention provides a secondary battery comprising the aforementioned positive electrode sheet.

[0019] By applying the technical solution of this invention, niobium (Nb) and boron (B) are used as co-doping elements. By controlling the doping amount within an extremely low molar ratio range, optimizing the lithium metal ratio and the ratio of ternary metal components, and ensuring the atomic-level uniform distribution of Nb and B atoms in the crystal structure, the aim of synergistically stabilizing the crystal lattice, suppressing cation mixing, and promoting lithium ion migration is achieved without destroying the layered structure. This results in a significant improvement in capacity retention, enhanced rate performance, and reduced structural degradation under high-voltage cycling. Attached Figure Description

[0020] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0021] Figure 1 This is a scanning electron microscope (SEM) image of the sintered material obtained in Example 1 of the present invention.

[0022] Figure 2 This is a SEM image of the primary sintered material obtained in Comparative Example 1 of this invention.

[0023] Figure 3 This is a SEM image of the primary sintering material obtained in Comparative Example 2 of this invention.

[0024] Figure 4 This is a SEM image of the primary sintered material obtained in Comparative Example 3 of this invention. Detailed Implementation

[0025] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0026] As described in the background section, existing ternary cathode materials suffer from insufficient single-crystal growth kinetics, poor crystal structure, and lag in lithium-ion transport kinetics. To address these issues, a first aspect of this invention provides a niobium-boron co-modified ternary cathode material with the chemical formula Li. a (Ni x Co y Mn z ) 1-b-c Nb b B cO2, where 1.0≤a≤1.10, 0.6≤x<1, 0.01≤y≤0.2, 0.01≤z≤0.3, x+y+z=1, 0<b≤0.00006, 0<c≤0.0003.

[0027] In nickel-cobalt-manganese ternary cathode materials, modified ternary lithium-ion battery cathode materials are prepared by introducing specific amounts of niobium (Nb) and boron (B) for co-modification and combining it with niobium and boron coating processes, exhibiting excellent electrochemical performance. B primarily acts as a pinning agent on the material surface, while Nb primarily acts on the bulk phase, enhancing bulk diffusion. Specifically, the synergistic effect of niobium and boron effectively induces the directional growth of single-crystal particles, resulting in a uniform increase in particle size and reducing grain boundary defects and surface side-reaction active sites. This optimized particle size growth directly enhances the stability of the crystal structure and significantly accelerates the transport kinetics of lithium ions in the bulk phase, laying a crucial foundation for a comprehensive improvement in electrochemical performance. The resulting niobium-boron co-modified ternary cathode material possesses excellent electrical performance while simultaneously enhancing structural integrity and thermal safety: the increased size of the single-crystal particles reduces interfacial stress, allowing the material to maintain structural integrity during deep cycling and significantly reducing the risk of thermal runaway.

[0028] In several preferred embodiments, in the chemical formula of the niobium-boron co-modified ternary cathode material, 0.00002 < b ≤ 0.00006, and 0.0002 < c ≤ 0.0003. Within this preferred range of 0.00002 < b ≤ 0.00006, Nb 5+ It can form a stable MO-Nb strong covalent bond network at the bulk transition metal sites, more effectively suppressing the phase transformation driving force of the layered structure to the spinel or rock salt phase during high-voltage delithiation, while significantly reducing Ni 2+ To Li + The tendency for layer migration (i.e., more effective suppression of cation mixing). Within the preferred concentration range of 0.0002 < c ≤ 0.0003, B... 3+ It can more fully combine with surface oxygen atoms to form a dense BO amorphous passivation layer, thereby more effectively blocking the corrosion of the positive electrode surface by HF in the electrolyte, inhibiting the dissolution of transition metals, and further reducing the oxidative decomposition of the electrolyte under high voltage.

[0029] Based on this, in several more preferred embodiments, the niobium-boron co-modified ternary cathode material is further preferably selected from Li. 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99967 Nb 0.00003 B 0.0003 O2, Li 1.05 (Ni 0.65 Co0.1 Mn 0.25 ) 0.99964 Nb 0.00006 B 0.0003 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99976 Nb 0.00004 B 0.0002 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99968 Nb 0.00002 B 0.0003 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99977 Nb 0.00003 B 0.0002 One or more of O2. Among these preferred chemical formulas, Nb and B exhibit better synergistic effects. Nb can maintain the rigidity of the crystal lattice structure in the bulk phase, while B constructs a dense barrier on the surface, thereby enabling the niobium-boron co-modified ternary cathode material to possess both high specific capacity and excellent long cycle life over a wide voltage window.

[0030] A second aspect of the present invention provides a method for preparing the above-mentioned niobium-boron co-modified ternary cathode material, comprising: step S1, wherein a precursor, a lithium source, a first niobium source, and a first boron source are subjected to a first sintering treatment to obtain a first material; step S2, wherein the first material, a second niobium source, and a second boron source are subjected to a dispersion treatment, a freeze-microwave treatment, and a second sintering treatment in sequence to obtain a second material; and step S3, wherein the second material and a third boron source are subjected to a third sintering treatment to obtain the niobium-boron co-modified ternary cathode material.

[0031] The preparation method provided by this invention employs a three-stage stepwise sintering process. Through the synergistic design of steps S1, S2, and S3, the gradient distribution of niobium and boron in the bulk phase, near-surface layer, and surface of the material is controlled. In step S1, the precursor, lithium source, first niobium source, and first boron source are sintered at high temperature, promoting the uniform incorporation of niobium and boron atoms into the lattice phase to form a stable primary sintered material. In step S2, the first material, along with the second niobium source and the second boron source, is subjected to ultrasonic-assisted wet ball milling in anhydrous ethanol, causing niobium and boron to uniformly adhere to the surface of the primary particles in the form of nanoscale compounds. Controllable solvent removal is then achieved through freeze-microwave gradient drying, avoiding agglomeration and component segregation during traditional drying processes. A second sintering process is then performed, promoting the formation of a dense transition layer coating structure of niobium and boron on the surface, rather than isolated agglomerates. In step S3, only the third boron source is introduced and sintered, allowing boron to selectively diffuse to the outermost lattice layer of the material, forming an extremely thin boron-oxygen passivation layer. The aforementioned process path ensures that niobium primarily acts on the bulk phase of the lattice, enhancing structural stability; while boron acts in stages on the near-surface and surface layers, respectively strengthening interfacial mechanical toughness and inhibiting electrolyte erosion. Thus, the resulting ternary cathode material maintains high capacity while significantly improving lattice integrity and interfacial stability during cycling, achieving synergistic structural strengthening from the bulk phase to the surface, thereby systematically improving the electrochemical durability of the ternary cathode material under high voltage.

[0032] In the preparation process, the following preferred combinations are used: In step S1, based on the weight of the precursor (100%), the amount of niobium added to the first niobium source is 0.05%~0.3%; and / or, the weight ratio of niobium in the first niobium source to boron in the first boron source is (0.8~1.2):(0.8~1.2); In step S2, the weight ratio of the first material, the niobium in the second niobium source, and the boron in the second boron source is 1:(0.001~0.005):(0.0005~0.001); In step S3, based on the weight of the second material (100%), the amount of boron added to the third boron source is 0.01%~0.03%. Based on the above preferred scheme, step S1 promotes the uniform incorporation of niobium and boron in the bulk phase at an atomically compatible ratio close to 1:1, reducing lattice distortion or charge imbalance caused by excess of a single element. At the same time, this ratio range can also promote the dense growth of single crystal particles, further improving the orderliness of the unit cell structure. In step S2, the preferred weight ratio of the first material to the second niobium source and the second boron source promotes more uniform adsorption of niobium and boron on the surface of the primary particles in the form of nanoscale oxides or hydroxyl compounds without forming a thick insulating phase, providing a better precursor basis for the subsequent low-temperature sintering to form a continuous coating layer. In step S3, the preferred range of boron content in the third boron source relative to the mass of the second material ensures that boron diffuses only into the outermost 1-2 lattice units, forming an atomic-level BO bond network, thereby more effectively suppressing the generation of surface oxygen vacancies and the dissolution of transition metals. In summary, the synergistic effect of the above-mentioned ratio ranges enables niobium to stabilize the lattice in the bulk phase and boron to passivate the interface on the surface. Both exert greater efficiency within their respective functional regions, ultimately significantly improving the structural integrity and interface stability of the resulting ternary material during high-voltage cycling.

[0033] Furthermore, in step S1, in order to promote the complete decomposition of the lithium source and its solid-phase reaction with the precursor, initiate the orderly formation of the layered structure, and more effectively suppress Ni... 2+ The migration towards the Li layer reduces the degree of cation mixing. Preferably, the sintering temperature of the first sintering treatment is 650℃~950℃, the sintering time is 5h~25h, and the first sintering treatment is carried out in an oxygen atmosphere; and / or, the heating rate of the first sintering treatment is 2℃ / min~7℃ / min. This allows the final first material to achieve high crystallinity while maintaining a more ideal layered structure, providing a more uniform and less defective matrix for subsequent steps, ultimately resulting in a ternary cathode material with superior structural reversibility and capacity retention during electrochemical cycling.

[0034] In step S1 above, the first sintering process is further preferably performed in two stages in an oxygen atmosphere, with the first stage having a sintering temperature of 650℃~750℃ and a sintering time of 5h~10h, and the second stage having a sintering temperature of 800℃~950℃ and a sintering time of 10h~15h. This preferred segmented process allows the obtained first material to achieve ideal grain size and morphology while preserving the integrity of the layered structure to a greater extent. This provides a high-quality parent material with a more stable structure and lower defect density for subsequent niobium and boron co-doping and coating, thereby significantly improving the structural stability and cycle life of the cathode material under high-voltage cycling. Specifically, the cell volume of the primary particles of the obtained first material is 33.80 Å. 3 ~34.10Å 3 The primary particles have a sphericity of 0.7–0.98, an aspect ratio of 1.0–1.3, and a particle size of 1.4–2.4 μm. The preferred cell volume range indicates that the primary material does not undergo significant lattice expansion or contraction after doping, maintaining a stable layered structure and providing a more uniform migration channel for lithium-ion insertion / extraction. The preferred sphericity range indicates that the primary material particles are nearly spherical with uniform surface curvature, reducing stress concentration points and further lowering the probability of microcrack initiation during cycling. The preferred aspect ratio range indicates that the primary material particles have a near-equiaxed morphology, without obvious rod-like or plate-like orientations, which is more conducive to uniform coating of the electrode slurry and achieving high compaction density. The preferred particle size range implies a more suitable specific surface area, thereby further optimizing rate performance. The synergistic optimization of the above morphology and structural parameters significantly reduces grain boundary defects and particle breakage risk in the final ternary material, thereby further improving its mechanical stability and interface durability during high-voltage cycling.

[0035] In step S2, to promote the in-situ formation of a denser and more uniform transition metal oxide / boron oxide thin layer on the particle surface by the second niobium source and the second boron source, the sintering temperature of the second sintering treatment is preferably 500℃~700℃, the sintering time is preferably 2h~8h, and the second sintering treatment is carried out in an oxygen atmosphere. This results in a more significant reduction in interfacial side reactions while maintaining high capacity in the final ternary cathode material, thereby more effectively improving long-cycle stability and thermal safety.

[0036] In several typical implementations, the preferred dispersion treatment in step S2 is ultrasonic-assisted wet ball milling, with a ball-to-material ratio of (1~5):1, a solid-to-liquid ratio of 1:(3~10), a milling speed of 200 r / min~500 r / min, an ultrasonic power of 100 W~500 W, and a mixing time of 2 h~5 h. Based on the synergistic effect of ultrasound and ball milling, a more uniform pre-coating layer is formed, providing a more uniform precursor for subsequent freeze-microwave drying and low-temperature sintering, resulting in a denser and more continuous final coating layer, thereby significantly enhancing the chemical stability and electrolyte erosion resistance of the final cathode material surface.

[0037] In several typical embodiments, the preferred step S2, the freeze-microwave treatment, includes sequentially subjecting the mixed slurry obtained from the dispersion treatment to a freeze stage, a first microwave stage, and a second microwave stage. The freeze treatment causes the solvent in the mixed slurry to freeze more thoroughly into ice crystals, forming a uniform microstructure framework and more effectively fixing the distribution of the coating on the particle surface. Subsequently, the ice crystals sublimate in the first microwave stage, and the second microwave stage further removes residual trace amounts of solvent, while also ensuring that the coating layer maintains nanoscale uniformity, continuity, and high adhesion after drying. Further preferred embodiments include: a freeze stage at a temperature of -40℃ to -20℃, a vacuum of 10Pa to 100Pa, and a time of 2h to 4h; and / or, a first microwave stage using a microwave power of 50W to 150W, a temperature of 30℃ to 50℃, and a time of 0.5±0.1h; and / or, a second microwave stage using a microwave power of 150W to 300W, a temperature of 60℃ to 80℃, and a time of 0.5±0.1h. The synergistic optimization of the above process parameters enables the construction of a denser, more continuous, and crack-free nanoscale coating layer by more precisely controlling phase change and energy input. This allows for more effective separation of surface modification and bulk doping functions, further suppressing electrolyte erosion and transition metal dissolution in the final ternary cathode material during application and improving its cycle life.

[0038] Furthermore, to promote the selective diffusion of boron to the outermost layer of the material at extremely low concentrations, and to significantly reduce the electron density of surface active sites while suppressing lattice oxygen escape, thereby further reducing electrolyte oxidative decomposition, in step S3, the sintering temperature of the third sintering treatment is preferably 200℃~500℃, the sintering time is preferably 2h~8h, and the third sintering treatment is carried out in an oxygen atmosphere. Thus, in synergy with the parameters in steps S1 and S2, the resulting niobium-boron co-modified ternary material maintains a lower interfacial impedance increase during high-voltage cycling, while also more effectively retaining its high specific capacity characteristics.

[0039] In practical applications, the first niobium source and the second niobium source are each independently added in the form of at least one of nitrate, acetate, chloride, and oxide; and / or, the first boron source, the second boron source, and the third boron source are each independently boric acid and / or boron oxide; and / or, the precursor has the chemical formula Ni x Co y Mn z (OH)₂, wherein 0.6≤x<1, 0.01≤y≤0.2, 0.01≤z≤0.3, and x+y+z=1; and / or, the lithium source is selected from one or more of lithium chloride, lithium acetate, lithium hydroxide, and lithium carbonate; and / or, the molar ratio of lithium element in the lithium source to the molar ratio of all metal elements in the precursor is (1~1.10):1. Based on this optimization of raw material combination and ratio, the above preparation process can maintain a controllable chemical environment, clear reaction path, few impurities, and high product purity in each step, thereby enabling the final niobium-boron co-modified ternary material to have better electrochemical consistency.

[0040] A third aspect of the present invention provides a positive electrode sheet comprising the aforementioned niobium-boron co-modified ternary positive electrode material; or, the positive electrode sheet comprising a niobium-boron co-modified ternary positive electrode material prepared by the aforementioned method for preparing the niobium-boron co-modified ternary positive electrode material. Because the niobium-boron co-modified ternary material provided by the present invention has a single-crystal structure without grain boundaries, combined with niobium stabilizing the crystal lattice and suppressing phase transitions in the bulk phase, and boron forming a dense oxygen network on the surface, it effectively suppresses the continuous oxidative decomposition of the electrolyte and the dissolution of transition metals under high voltage, resulting in a thinner electrode / electrolyte interface film with a more uniform composition and slower impedance growth. Therefore, the corresponding positive electrode sheet exhibits significantly better interface stability and cycle durability than conventional materials after assembly.

[0041] A fourth aspect of the present invention provides a secondary battery comprising the aforementioned positive electrode sheet. The battery system constructed using the niobium-boron co-modified ternary positive electrode material provided by the present invention exhibits superior overall electrochemical performance: higher first-cycle coulombic efficiency, better rate performance, and superior cycle performance.

[0042] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0043] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0044] Example 1

[0045] A method for preparing a niobium-boron co-modified ternary cathode material:

[0046] (S1), Ni, a nickel-cobalt-manganese precursor 0.65 Co 0.1 Mn 0.25 (OH)2 and Li2CO3 were dry-mixed in a molar ratio of 1:1.05 (where the molar amount of Li2CO3 was calculated based on the molar amount of Li). Then, Nb2O5 and H3BO3 were added to the primary material, with Nb and B each accounting for 0.2% of the total mass of the precursor (i.e., the weight ratio of niobium in the first niobium source to boron in the first boron source was 1:1). After uniform mixing, the material was placed in an oxygen atmosphere for high-temperature sintering treatment at a heating rate of 2℃ / min, a pre-sintering temperature of 650℃, and a sintering time of 5h. The temperature was then raised to 925℃ and sintered for 15h to obtain the sintered product. The sintered product was ground into powder to obtain the ternary single-crystal cathode material co-doped with niobium and boron in the primary sintered material.

[0047] The obtained primary sintered material was subjected to XRD and SEM tests. The cell volume of the primary particles obtained after XRD refinement was 34.08 Å. 3 The SEM morphology of the sintered material is as follows: Figure 1 As shown, SEM revealed that the primary particle size was approximately 2.26 μm, the roundness of the primary particles was 0.92, and the aspect ratio was 1.2.

[0048] (S2) The primary sintering material obtained in step (S1) is mixed with Nb2O5 and H3BO3, wherein Nb and B elements account for 0.1% and 0.05% of the total mass of the primary sintering material, respectively (i.e., the weight ratio of niobium element in the first material, the second niobium source, and the second boron source is 1:0.001:0.0005). The mixture was prepared by ultrasonic-assisted high-energy ball milling wet mixing with a ball-to-material ratio of 2:1, a solid-to-liquid ratio of 1:3, a rotation speed of 300 r / min, an ultrasonic power of 350 W, and a mixing time of 5 h to obtain a uniformly dispersed slurry. The slurry was then pre-frozen at -30℃ for 3 h with a vacuum degree controlled at 10~100 Pa. It was then treated at 50℃ with a microwave power of 80 W and at 80℃ with a microwave power of 150 W for 0.5 h respectively. The solvent was removed by step drying. The mixture was then sintered in an oxygen atmosphere in a furnace. The temperature was increased from room temperature to 650℃ at a rate of 2℃ / min and held for 5 h. The mixture was then naturally cooled to room temperature to obtain the secondary modified material.

[0049] S3. Mix the secondary modified material obtained in S1 with H3BO3 evenly, wherein the B element accounts for 0.03% of the total mass of the secondary sintering modified material. Then, under an oxygen atmosphere, heat the material from room temperature to 400℃ at a heating rate of 2℃ / min, hold it at that temperature for 5 hours, and then allow it to cool naturally to room temperature. After sieving and demagnetizing, the modified ternary cathode material is obtained.

[0050] The chemical formula of the obtained ternary cathode material is Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99967 Nb 0.00003 B 0.0003 O2 was subjected to XRD and SEM tests. XRD showed that the cell volume of the primary particles was 34.08 Å. 3 SEM showed that the primary particle size was approximately 2.26 μm, the roundness of the primary particles was 0.94, and the aspect ratio was 1.1.

[0051] Example 2

[0052] The only difference between this embodiment and Embodiment 1 is the amount of niobium and boron sources added in each step. Specifically:

[0053] In step (S1), Nb accounts for 0.05% of the total mass of the precursor, and B accounts for 0.3% of the total mass of the precursor.

[0054] In step (S2), the weight ratio of niobium in the first material, niobium in the second niobium source, and boron in the second boron source is 1:0.005:0.0005;

[0055] In step (S3), element B accounts for 0.01% of the total mass of the secondary sintering modified material.

[0056] The cell volume of the primary particles of the obtained primary sintered material is 34.09 Å. 3 The primary particle size is approximately 1.76 μm, the roundness of the primary particles is 0.90, and the aspect ratio is 1.1.

[0057] The chemical formula of the obtained ternary cathode material is Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99964 Nb 0.00006 B 0.0003 O2.

[0058] Example 3

[0059] The only difference between this embodiment and Embodiment 1 is the amount of niobium and boron sources added in each step. Specifically:

[0060] In step (S1), Nb accounts for 0.3% of the total mass of the precursor, and B accounts for 0.05% of the total mass of the precursor.

[0061] In step (S2), the weight ratio of niobium in the first material, niobium in the second niobium source, and boron in the second boron source is 1:0.001:0.001;

[0062] In step (S3), element B accounts for 0.03% of the total mass of the secondary sintering modified material.

[0063] The cell volume of the primary particles of the obtained primary sintering material is 34.08 Å. 3 The primary particle size is approximately 1.84 μm, with a roundness of 0.93 and an aspect ratio of 1.2. The chemical formula of the resulting ternary cathode material is Li. 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99976 Nb 0.00004 B 0.0002 O2.

[0064] Example 4

[0065] The difference between this embodiment and Embodiment 1 lies only in the sintering treatment in step (S1). Specifically, after the mixture is homogeneous, the material is placed in an oxygen atmosphere for high-temperature sintering treatment. The heating rate is 2℃ / min, the pre-sintering temperature is 650℃, the sintering time is 10h, and then the temperature is raised to 950℃ and sintered for 10h to obtain the sintered product.

[0066] The cell volume of the primary particles of the obtained primary sintered material is 34.04 Å. 3 The primary particle size is approximately 2.40 μm, with a roundness of 0.97 and an aspect ratio of 1.2. The chemical formula of the resulting ternary cathode material is Li. 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99967 Nb 0.00003 B 0.0003 O2.

[0067] Example 5

[0068] The difference between this embodiment and Embodiment 1 lies only in the sintering treatment in step (S1). Specifically, after the mixture is homogeneous, the material is placed in an oxygen atmosphere for high-temperature sintering treatment. The heating rate is 7°C / min, the pre-sintering temperature is 750°C, the sintering time is 5h, and then the temperature is raised to 800°C for sintering for 15h to obtain the sintered product.

[0069] The cell volume of the primary particles of the obtained primary sintered material is 34.09 Å. 3 The primary particle size is approximately 1.80 μm, the roundness of the primary particles is 0.92, and the aspect ratio is 1.05. The chemical formula of the resulting ternary cathode material is Li. 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99967Nb 0.00003 B 0.0003 O2.

[0070] Example 6

[0071] The difference between this embodiment and Embodiment 1 lies only in the freeze-microwave treatment in step (S2). Specifically, the sample is pre-frozen at -40°C for 1 hour, with the vacuum degree controlled at 10~100Pa, then treated at 50°C with a microwave power of 50W for 0.5 hours, and then treated at 60°C with a microwave power of 300W for 0.5 hours, followed by step drying to remove the solvent.

[0072] Example 7

[0073] The difference between this embodiment and Embodiment 1 lies only in the freezing-microwave treatment in step (S2). Specifically, the sample is pre-frozen at -20°C for 5 hours, with the vacuum degree controlled at 10~100Pa, then treated at 30°C and microwave power of 150W for 0.5 hours, and then treated at 80°C and microwave power of 150W for 0.5 hours, followed by step drying to remove the solvent.

[0074] Example 8

[0075] The only difference between this embodiment and Embodiment 1 is the sintering process in step (S2), specifically: the temperature is increased from room temperature to 500°C at a heating rate of 2°C / min, and held for 8 hours.

[0076] Example 9

[0077] The only difference between this embodiment and Embodiment 1 is the sintering process in step (S2), specifically: the temperature is increased from room temperature to 700°C at a heating rate of 2°C / min, and held for 2 hours.

[0078] Example 10

[0079] The difference between this embodiment and Embodiment 1 lies only in the sintering process in step (S3). Specifically, under an oxygen atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 2°C / min and held for 2 hours.

[0080] Example 11

[0081] The only difference between this embodiment and Embodiment 1 is that in step (S1), the amount of niobium source added is changed to 0.1% of the total mass of the precursor.

[0082] The chemical formula of the ternary cathode material obtained in this embodiment is Li. 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99968 Nb 0.00002 B 0.0003 O2.

[0083] Example 12

[0084] The only difference between this embodiment and Embodiment 1 is that in step (S1), the amount of boron source added is changed to 0.1% of the total mass of the precursor.

[0085] The chemical formula of the ternary cathode material obtained in this embodiment is Li. 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99977 Nb 0.00003 B 0.0002 O2.

[0086] Comparative Example 1

[0087] The only difference between this comparative example and Example 1 is that no niobium source and boron source were added in step (S1).

[0088] The SEM morphology of the obtained primary sintered material is as follows: Figure 2 As shown.

[0089] Comparative Example 2

[0090] The only difference between this comparative example and Example 1 is that no niobium source was added in step (S1).

[0091] The cell volume of the primary particles obtained after XRD refinement of the first material in this comparative example is 34.14 Å. 3 The SEM morphology of the obtained primary sintered material is as follows: Figure 3 As shown in the figure, SEM reveals that no single crystals were formed from the primary particles.

[0092] Comparative Example 3

[0093] The only difference between this comparative example and Example 1 is that no boron source was added in step (S1), and the SEM morphology of the resulting primary sintered material is as follows. Figure 4 As shown.

[0094] Comparative Example 4

[0095] The only difference between this comparative example and Example 1 is that no niobium source or boron source was added in either step (S1) or step (S2).

[0096] Battery sample assembly and performance testing method: The materials prepared in the above-mentioned examples and comparative examples were used as positive electrode active materials, and conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 90:5:5 and dissolved in N-methylpyrrolidone solution. The mixture was then uniformly coated onto aluminum foil and dried at 120°C for 12 hours to obtain a compacted density of 3.5 g / cm³. 3The positive electrode was prepared using a 1.0 mol / L LiPF6 solution dissolved in an EC / DMC / DEC (1:1:1, by mass fraction wt.%) electrolyte. The positive electrode, separator (Celgard 24), electrolyte, and lithium metal negative electrode were assembled into a CR2016 coin cell in a glove box. The assembled coin cell was subjected to electrochemical performance tests at 25°C, with an initial voltage of 2.8V and a cutoff voltage of 4.5V. For the first four weeks, the battery was charged and discharged sequentially at rates of 0.2C / 0.2C, 0.33C / 0.33C, 1C / 1C, and 0.2C / 0.2C, respectively. Then, it was charged and discharged at a rate of 1C / 1C until 50 cycles were completed. The test results are shown in Table 1.

[0097] Table 1

[0098]

[0099] As can be seen from the above description, the embodiments of the present invention prepare a niobium-boron co-modified ternary single-crystal cathode material by doping a specific amount of niobium and boron into the cathode material and then coating it with niobium and boron. The co-modification of boron and niobium promotes single-crystal growth, enhances the crystal structure, and accelerates lithium-ion transport. After modification, the resulting cathode material maintains high capacity while significantly improving cycle stability, structural integrity, and thermal safety. It exhibits excellent cycle performance and rate performance within a high voltage range of 2.8~4.5V. Furthermore, the process employed in this invention is simple and easy to control, with a high yield, which is conducive to its promotion and application in large-scale industrial production.

[0100] In the table above, it can be seen from the data of Example 1 and Comparative Example 4 that the modified ternary cathode material prepared by the present invention has a significant improvement effect on the capacity, rate performance and cycle performance of the material; at the same time, comparing Example 1 with Examples 11 and 12, it can be seen that changes in the doping and coating ratio of Nb and B will affect the capacity performance of the material and the capacity retention rate will also decrease.

[0101] The average primary particle size of Example 1 was 2.26 μm, while the average primary particle size of Comparative Examples 1 and 3 was too small. Comparative Example 2, which was doped with B, did not form a single crystal after calcination. This further illustrates that the doping of Nb and B in a specific ratio promoted the increase of primary particle size. By comparing the electrical performance data of Example 1 and Comparative Examples 1, 2, and 3, it can be seen that the use of Nb and B for co-modification also significantly accelerated the transport kinetics of lithium ions in the bulk phase of the material. In the high voltage range of 2.8-4.5V, it has excellent cycle performance and rate performance.

[0102] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in a sequence other than those described herein.

[0103] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A niobium-boron co-modified ternary cathode material, characterized in that, The chemical formula of the niobium-boron co-modified ternary cathode material is Li. a (Ni x Co y Mn z ) 1-b-c Nb b B c O2, where 1.0≤a≤1.10, 0.6≤x<1, 0.01≤y≤0.2, 0.01≤z≤0.3, x+y+z=1, 0<b≤0.00006, 0<c≤0.0003.

2. The niobium-boron co-modified ternary cathode material according to claim 1, characterized in that, In the chemical formula of the niobium-boron co-modified ternary cathode material, 0.00002 < b ≤ 0.00006, and 0.0002 < c ≤ 0.0003.

3. The niobium-boron co-modified ternary cathode material according to claim 1 or 2, characterized in that, The niobium-boron co-modified ternary cathode material is selected from Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99967 Nb 0.00003 B 0.0003 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99964 Nb 0.00006 B 0.0003 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99976 Nb 0.00004 B 0.0002 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99968 Nb 0.00002 B 0.0003 O2, Li 1.05 (Ni 0.65 Co 0.1 Mn 0.25 ) 0.99977 Nb 0.00003 B 0.0002 One or more of O2.

4. A method for preparing a niobium-boron co-modified ternary cathode material according to any one of claims 1 to 3, characterized in that, include: Step S1: The precursor, lithium source, first niobium source and first boron source undergo a first sintering treatment to obtain the first material; In step S2, the first material, the second niobium source, and the second boron source are subjected to dispersion treatment, freeze-microwave treatment, and second sintering treatment in sequence to obtain the second material; In step S3, the second material and the third boron source undergo a third sintering process to obtain the niobium-boron co-modified ternary cathode material.

5. The method for preparing the niobium-boron co-modified ternary cathode material according to claim 4, characterized in that, In step S1 Based on the weight of the precursor as 100%, the amount of niobium added to the first niobium source is 0.05%~0.3%; and / or, The weight ratio of niobium in the first niobium source to boron in the first boron source is (0.8~1.2):(0.8~1.2); and / or, The first sintering treatment is carried out at a sintering temperature of 650℃~950℃ and a sintering time of 5h~25h, and the first sintering treatment is carried out in an oxygen atmosphere; and / or, The heating rate of the first sintering treatment is 2℃ / min to 7℃ / min.

6. The method for preparing the niobium-boron co-modified ternary cathode material according to claim 4 or 5, characterized in that, In step S1, the first sintering process includes a first stage and a second stage performed sequentially in an oxygen atmosphere, wherein the sintering temperature of the first stage is 650℃~750℃ and the sintering time is 5h~10h, and the sintering temperature of the second stage is 800℃~950℃ and the sintering time is 10h~15h. Preferably, the cell volume of the primary particles of the first material is 33.80 Å. 3 ~34.10Å 3 The roundness of the primary particles is 0.7~0.98, the aspect ratio is 1.0~1.3, and the particle size is 1.4μm~2.4μm.

7. The method for preparing the niobium-boron co-modified ternary cathode material according to any one of claims 4 to 6, characterized in that, In step S2 The weight ratio of niobium in the first material, the second niobium source, and the second boron source is 1:(0.001~0.005):(0.0005~0.001); and / or, The second sintering treatment is carried out at a sintering temperature of 500℃~700℃ and a sintering time of 2h~8h, and the second sintering treatment is carried out in an oxygen atmosphere.

8. The method for preparing the niobium-boron co-modified ternary cathode material according to any one of claims 4 to 7, characterized in that, In step S2 The dispersion treatment method is ultrasonic-assisted wet ball milling, and the ball-to-material ratio used in the ultrasonic-assisted wet ball milling is (1~5):1, the solid-liquid ratio is 1:(3~10), the ball milling speed is 200r / min~500r / min, the ultrasonic power is 100W~500W, and the mixing time is 2h~5h. And / or, The freeze-microwave treatment includes: sequentially subjecting the mixed slurry obtained from the dispersion treatment to a freeze stage, a first microwave stage, and a second microwave stage; Preferably, the freezing stage is performed at a temperature of -40°C to -20°C, a vacuum of 10Pa to 100Pa, and a duration of 2h to 4h; and / or, the microwave power used in the first microwave stage is 50W to 150W, the temperature is 30°C to 50°C, and the duration is 0.5±0.1h; and / or, the microwave power used in the second microwave stage is 150W to 300W, the temperature is 60°C to 80°C, and the duration is 0.5±0.1h.

9. The method for preparing the niobium-boron co-modified ternary cathode material according to any one of claims 4 to 8, characterized in that, In step S3 Based on the weight of the second material as 100%, the amount of boron added to the third boron source is 0.01%~0.03%; and / or, The third sintering treatment is carried out at a sintering temperature of 200℃~500℃ and a sintering time of 2h~8h, and the third sintering treatment is carried out in an oxygen atmosphere.

10. The method for preparing the niobium-boron co-modified ternary cathode material according to any one of claims 4 to 9, characterized in that, The first niobium source and the second niobium source are each independently added in the form of at least one of nitrate, acetate, chloride, and oxide; and / or, The first boron source, the second boron source, and the third boron source are each independently boric acid and / or boron oxide; and / or, The precursor has the chemical formula Ni x Co y Mn z (OH)₂, where 0.6 ≤ x < 1, 0.01 ≤ y ≤ 0.2, 0.01 ≤ z ≤ 0.3, and x + y + z = 1; and / or, The lithium source is selected from one or more of lithium chloride, lithium acetate, lithium hydroxide, and lithium carbonate; and / or, The molar ratio of lithium in the lithium source to the molar ratio of all metal elements in the precursor is (1~1.10):

1.

11. A positive electrode sheet, characterized in that, The positive electrode sheet includes the niobium-boron co-modified ternary positive electrode material according to any one of claims 1 to 3; or, the positive electrode sheet includes the niobium-boron co-modified ternary positive electrode material prepared by the preparation method of the niobium-boron co-modified ternary positive electrode material according to any one of claims 4 to 10.

12. A secondary battery, characterized in that, The secondary battery includes the positive electrode sheet as described in claim 11.